Phagocytosis is a primary determinant of pulmonary clearance of clinical Klebsiella pneumoniae isolates - van der Geest, Rick; Fan, Hongye; Peñaloza, Hernán F.; Bain, William G.; Xiong, Zeyu; Kohli, Naina; Larson, Emily; Sullivan, Mara L. G.; Franks, Jonathan M.; Stolz, Donna B.; Ito, Ryota; Chen, Kong; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Klebsiella pneumoniae (Kp) is a common cause of hospital-acquired pneumonia. Although previous studies have suggested that evasion of phagocytic uptake is a virulence determinant of Kp, few studies have examined phagocytosis sensitivity in clinical Kp isolates. We screened 19 clinical respiratory Kp isolates that were previously assessed for mucoviscosity for their sensitivity to macrophage phagocytic uptake, and evaluated phagocytosis as a functional correlate of in vivo Kp pathogenicity. The respiratory Kp isolates displayed heterogeneity in the susceptibility to macrophage phagocytic uptake, with 14 out of 19 Kp isolates displaying relative phagocytosis-sensitivity compared to the reference Kp strain ATCC 43816, and 5 out of 19 Kp isolates displaying relative phagocytosis-resistance. Intratracheal infection with the non-mucoviscous phagocytosis-sensitive isolate S17 resulted in a significantly lower bacterial burden compared to infection with the mucoviscous phagocytosis-resistant isolate W42. In addition, infection with S17 was associated with a reduced inflammatory response, including reduced bronchoalveolar lavage fluid (BAL) polymorphonuclear (PMN) cell count, and reduced BAL TNF, IL-1, and IL-12p40 levels. Importantly, host control of infection with the phagocytosis-sensitive S17 isolate was impaired in alveolar macrophage (AM)-depleted mice, whereas AM-depletion had no significant impact on host defense against infection with the phagocytosis-resistant W42 isolate. Altogether, these findings show that phagocytosis is a primary determinant of pulmonary clearance of clinical Kp isolates.